2020
DOI: 10.1155/2020/4106949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SoundBite Bone Conduction Hearing Aids on Speech Recognition and Quality of Life in Patients with Single-Sided Deafness

Abstract: Objectives. To analyze the clinical application of SoundBite bone conduction hearing aids by assessing the improvement of speech recognition and the scores of the benefit scale questionnaire for patients with single-sided deafness (SSD). Design. Nine patients aged 24 to 61 years with SSD for more than 3 months were enrolled in this study. The patients could understand and repeat Mandarin and have good compliance with the study. The measurements were evaluated before and after one month of wearing hearing aids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Additionally, there is a removable device inside the mouth (ITM), specially designed to fit comfortably in the upper back teeth, which receives the signals processed by the BTE device, converting them into vibrations, which stimulate the cochlea, allowing the user to perceive the sound. According to a study conducted by Lou et al [79] on nine patients with SSD, SoundBite has been shown to lead to improved speech recognition and overall quality of life in both quiet and noisy environments.…”
Section: Bone Conduction Devices (Bcd): Extrinsic Devicesmentioning
confidence: 99%
“…Additionally, there is a removable device inside the mouth (ITM), specially designed to fit comfortably in the upper back teeth, which receives the signals processed by the BTE device, converting them into vibrations, which stimulate the cochlea, allowing the user to perceive the sound. According to a study conducted by Lou et al [79] on nine patients with SSD, SoundBite has been shown to lead to improved speech recognition and overall quality of life in both quiet and noisy environments.…”
Section: Bone Conduction Devices (Bcd): Extrinsic Devicesmentioning
confidence: 99%
“…Additionally, there is a removable device inside the mouth (ITM), specially designed to fit comfortably in the upper back teeth, which receives the signals processed by the BTE device, converting them into vibrations, which stimulate the cochlea and allow the user to perceive the sound. According to the study conducted by Lou et al [66] on nine patients with SSD, SoundBite has been shown to lead to improved speech recognition and overall quality of life in both quiet and noisy environments.…”
Section: Bone Conduction Devices (Bcd): Extrinsic Devicesmentioning
confidence: 99%